TINJAUAN PELAKSANAAN PEKERJAAN ABUTMENT PEMBANGUNAN FLYOVER GELUMBANG PADA BATAS KAB. OGAN ILIR / BATAS KAB. MUARA ENIM – BATAS KOTA PRABUMULIH (PROVINSI SUMATERA SELATAN) - Luthfi Rusdani, Muhammad; Wahab, Wahyuni (Ensiklopedia of Journal, 2024)
A bridge is a construction structure made to cross ravines or obstacles such as rivers, lakes, rivers, railways or highways, the construction of the Fly Over is motivated by frequent long traffic jams. With the increase in transportation in the area that causes traffic jams and hampered economic activities from one region to another that almost every day occurs, thus the Palembang city government works Similar to the Muara Enim Regency Government also trying to break down the congestion that exists in Gelumbang District and in Palembang City, the construction will be carried out around the railway crossing on the Palembang - Prabumulih causeway as well as connecting Ogan Ilir Regency / Muara Enim Regency.Keywords:  Abutment for Fly Over construction.